John Wesley Hunt : Pioneer Merchant, Manufacturer and Financier - Ramage, James A. (Book collections on Project MUSE., 2009)
When John Wesley Hunt came to Kentucky in 1794, his plan was to open a general store in Lexington. A canny judge of business opportunity, he soon expanded his activities and became one of the responsible figures of Kentucky banking and finance. In another kind of venture, he imported fine stallions from the East, significantly improving the bloodlines of thoroughbreds and trotters in the Bluegrass. John Wesley Hunt tells the story of Hunt's business exploits against the background of life in frontier Lexington. James A. Ramage reveals how his innovative solutions to the financial problems of.